Effect of Service Quality and Promotion on Purchase Decisions at Alfamart Driyorejo - Nuning Nurna Dewi (Jurnal Mantik, 2020)
At this time, the development of the times is felt to be very rapid, starting from a social, economic, political, cultural perspective, even consumption behavior in our society, in terms of consumer decisions to shop, it has shifted, the development of shopping centers is currently affecting the increasing number of places Modern shopping can be seen from the many competition in minimarkets and the mushrooming of the existence of minimarkets itself. Thus, it can be ascertained that the market wants to give the best to consumers by always trying to be able to meet the needs of its consumers. Quality of service and promotion is the main mission for a minimarket where the main objective is the consumer's decision to make a purchase transaction, where the existing purchases will bring profit to the producer. This study aims to identify and explain the factors that influence purchasing decisions at Alfamart Driyorejo. There are 2 variables used in this study, namely: the quality of the service and promotion. This research method uses quantitative methods with a population and sample of consumers Alfamart Driyorejo. The sample in this study were 100 respondents and the data were collected by distributing questionnaires. From the results of multiple linear regression analysis test data, the following results obtained Y = 0.392 + 0.133X2 + 0.509X3 + e, partial hypothesis testing for service quality variables obtained tcount <t table, namely 0.133 <2.699 and for promotional variables obtained tcount < t table is 0.509 <2,699 The results of hypothesis testing show that the variable service quality and promotion partially has a positive and significant effect on purchasing decisions, simultaneously the quality of service and promotion also has a positive and significant effect on purchasing decisions at Alfamart Driyorejo.